Approximate solution of linear differential equations of neutral type by aggregative-iterative method - Kostyshyn, L.P.; Bigun, Ya.J. (Carpathian Mathematical Publications, 2011)
This article is devoted to linear differential equation of neutral type with two-point boundary conditions. Iteration process for approximate solution is constructed by aggregation-iterative method and its convergence is proved.